Love's whipping boy - Barnes, Elizabeth (University of North Carolina Press, 2011)
Working to reconcile the Christian dictum to 'love one's neighbour as oneself' with evidence of U.S. sociopolitical aggression, including slavery and corporal punishment, the author suggests ways of understanding paradoxical relationships between empathy, violence, and religion.
10.5149/9780807877968_barnes
Keywords: Literatur; Gewalt; Mitleid; Empfindsamkeit; Nationalcharakter; American fiction; Violence in literature; Empathy in literature; Sentimentalism in literature; National characteristics; American; in literature